Cannabismissbrauch im Hochleistungssport - Mareck-Engelke, U.; Geyer, H.; Schänzer, W. (Deutsche Zeitschrift für Sportmedizin, 2001)
According to the IOC rules, the use of cannabinoids (e.g. Marijuana, Ha-shish) is forbidden and tests for cannabinoids will be conducted at the Olympic Games. The IOC, however, allows each Sport Organization to decide whether or not to place cannabinoids on their list of forbidden substances. A cut-off limit of 15 ng/mL for the main metabolite 11-nor—.9-te-trahydrocannabinol-9-carboxylic acid has been defined in order to avoid passive smoking. Positive Results due to prohibition of cannabinoids depend on behalf of the single federation. The extent of the use of cannabinoids in sports in 1998 and 1999 is presented here as well as the distribution by sport type and gender. Doping control urine samples from national and international federations were analyzed by gas chromatography/mass spectrometry (GC/MS). In 1998 as well as in 1999 the percentage of urine samples which contain more than 15 ng/mL of 11-nor—.9-tetrahydrocannabinol-9-carboxylic acid is similar (1998: 0.5% ; 1999: 0.6%). The female urine samples with positive cannabinoid cases is very low (3%). Most of the urine samples containing concentrations of THC-metabolite higher than 15 ng/mL originate from federations which have not banned cannabinoids. The rules of the different federations regarding the abuse of cannabinoids are still nonuniform.